HUBUNGAN PENGETAHUAN DAN SIKAP IBU MENGENAI GIZI SEIMBANG DENGAN STATUS GIZI ANAK BALITA - Najia Jamalatun Nisa; Revalita Wahab (Jurnal Akta Trimedika, 2024)
One of the health markers of childeren group underfives (0-60 months) are group of children is nutritional status because the level of vulnerability to nutritional problems in underfives is quite high. Maternal knowledge and attitude towards balanced nutrition are very important in preventing nutritional problems. The aim of this study was to determine the relationship of maternal knowledge and attitudes regarding balanced nutrition with nutritional status of underfives. The cross sectional study was conducted on  61 mothers and their toddlers. Sampling was taken by consecutive non-random sampling technique at Posyandu Kamajaya, Serang City, Banten Province. Data were collected using a questionnaire of maternal knowledge and attitude towards balanced nutrition and scales, microtoise or length board. The results of maternal knowledge towards balanced nutrition with nutritional status of underfives is p = 0.000 and the result of maternal attitude towards balanced nutrition with the nutritional status of underfives is p = 0.549. There was a statistically significant relationship of maternal knowledge towards balanced nutrition with nutritional status of underfives. Conclusions there was no statistically significant relationship of maternal attitude towards balanced nutrition and the nutritional status of underfives at Posyandu Kamajaya ,Serang City, Banten Province.